Prognostic Heterogeneity of MRE11 Based on the Location of Primary Colorectal Cancer Is Caused by Activation of Different Immune Signals - Fan, Chuan-Wen; Kopsida, Maria; Liu, You-Bin; Zhang, Hong; Gao, Jing-Fang; Arbman, Gunnar; Cao, Si-Yu-Wei; Li, Yuan; Zhou, Zong-Guang; Sun, Xiao-Feng (Frontiers in Oncology, 2020)
Background: MRE11 plays an important role in DNA damage response for the maintenance of genome stability, and is becoming a prognostic marker for cancers, including colorectal cancer (CRC). However, the correlations of MRE11 to prognosis and tumor-infiltrating inflammatory cells (TIICs) in different locations of CRC remains unclear. Methods: Among Swedish and TCGA-COREAD patients, we investigated the association of MRE11 expression, tumor-infiltrating inflammatory cells (TIICs) and microsatellite status with survival in right-sided colon cancer (RSCC) and left-sided colon and rectal cancer (LSCRC). The signaling of MRE11-related was further analyzed using weighted gene co-expression network analysis and ClueGO. Results: High MRE11 expression alone or combination of high MRE11 expression with high TIICs was related to favorable prognosis in LSCRC. Moreover, high MRE11 expression was associated with favorable prognosis in LSCRC with microsatellite stability. The relationships above were adjusted for tumor stage, differentiation and/or TIICs. However, no such evidence was observed in RSCC. Several signaling pathways involving MRE11 were found to be associated with cell cycle and DNA repair in RSCC and LSCRC, whereas, the activation of the immune response and necrotic cell death were specifically correlated with LSCRC. Conclusions: High MRE11 expression is an independent prognostic marker in LSCRC and enhanced prognostic potency of combining high MRE11 with high TIICs in LSCRC, mainly due to differential immune signaling activated by MRE11 in RSCC and LSCRC, respectively.